Does Korean drama have a real influence? An analysis of Malaysia outbound tourists to South Korea - Teh, Pek Yen *; Goh, H. C. (Cognizant Communication Corporation, 2016)
Korea has recently emerged as one of the top tourism destinations in the world, and a catalyst of its rapidly developing tourism industry is Korean drama. Studies on Korean tourism, which focus on sociocultural and gender-related issues, as well as audience behaviors, have been conducted in the Asian region. However, these studies have been geographically limited to monoethnic countries only. As one of the countries contributing to Korea’s inbound tourism, Malaysia experienced a significant increase of tourists visiting Korea. Hence, this study aims to identify the motivation segmentation and overall satisfaction level among Malaysian tourists visiting Korea. Specifically, the study aims to identify the influence of Korean drama in their overall experience. A questionnaire-based survey of these tourists was conducted in Seoul City, and cluster analysis was applied to derive motivation segmentation from the collected data. Afterwards, a characteristic comparison was accomplished between drama- and non-drama-watching tourists. Finally, the overall satisfaction of tourists was determined. Results showed three types of motivation segmentation and revealed characteristic differences between the drama- and non-drama-watching tourists. Furthermore, these segmented motivations manifested significant differences in terms of overall satisfaction. In general, Malaysian tourists perceived Korea as a place for family and social bonding, as well as for relaxation and cultural exploration. Interestingly, Korean drama did not influence the overall tourist satisfaction, although it serves as a cultural platform through which tourists gained familiarity with the destination prior to the trip.